Effects of ecosystems preservation on economic growth in China's coastal region: Multilevel modelling and exploration. (December 2021) - Li, Zehui; Wang, Jing; Kong, Xuesong; Zhang, Boen; Liu, Jingjing; Ding, Su; Du, Yingkun
Highlights: Test the impacts of ecosystem preservation on economic growth across multilevel. HEOCHGS tend to have more urban green space and less forest ecosystem. The negative effect of wetland is more robust than that of forest ecosystem. Urban green space is associated with increased economic growth. Nature reserve preservation show negative association with economic growth. Abstract: Ecosystems conservation is vital to social-economic and environmental sustainability. The relationship between ecosystems preservation and economic growth has been a popular topic worldwide. However, the economic effects of ecosystems preservation across multiple levels are unclear. This study analyzes the spatiotemporal characteristics of different ecosystems preservation, analyzing the correlations between ecosystem preservation and economic growth based on the method of "trading space for time", extending a multilevel modeling to explore the overall and the regional differentiation in economic effects of ecosystems preservation at multi-levels in the coastal region in China during the period 2000–2015. Results show an overall decline in different ecosystems and an increase in green coverage rate and urban green space across the coastal region. With the same type of growth speed, the higher the economic output, the smaller the forest, wetland, and other ecosystems, and the larger the urban green space. Multilevel modeling regression revealed that economic growth is influenced by ecosystems preservation and effects of ecosystems preservation differentials vary substantially across regions. Wetland and forest ecosystems preservation played a negative role, whereas urban greening in cities played a positive role in overall urban economic growth and economic growth of surrounding or non-surrounding cities of the provincial capital. Furthermore, nature reserves preservation presented a negative association with economic growth at the provincial level. The heterogeneities of ecosystems along with economic growth stages is imperative, as is differentiating ecosystem preservation objectives across coastal regions. This study might help to develop theories of ecosystems preservation in economic growth and may fill the gap in which previous research ignored the multilevel effects of ecosystems preservation. Therefore, it provides good strategies to implement effective sustainable ecosystems management and sustainable regional economic growth.